Equalization-Enhanced Phase Noise in Stokes-Vector Direct Detection Systems - Meng Qiu; Qunbi Zhuge; Mohammed Y. S. Sowailem; Thang M. Hoang; Mathieu Chagnon; Meng Xiang; Xingyu Zhou; Fangyuan Zhang; David V. Plant (IEEE Photonics Journal, 2016)
In this work, we provide both numerical and experimental investigations of equalization-enhanced phase noise (EEPN) in Stokes-vector direct detection (SV-DD) systems. We show that the influence of EEPN cannot be neglected in high symbol rate SV-DD systems after transmission over several hundred kilometers of fibers when electronic chromatic dispersion compensation and lasers with linewidths of the order of Megahertz are employed. Simulation results are presented to evaluate the dependence of EEPN effects on laser linewidth, transmission distance, and symbol rate. Experiments are then conducted in a 56-Gbaud 16-quadrature amplitude modulation (QAM) SV-DD system to demonstrate the EEPN-induced performance degradation after 320-km transmission over standard single mode fiber (SSMF).